Banking System Security and Efficiency as Drivers of Perceived Service Quality: The Mediating Role of Responsiveness - Hamal, Janga Bahadur; Chalise, Mahananda; Budhathoki, Prem Bahadur; Niroula, Arjun Kumar; Singh, Gobind Kumar (Nepal Journal of Multidisciplinary Research, 2025)
Background: In Nepal, the growing reliance on electronic banking has increased the importance of ensuring security, efficiency, and responsiveness in service delivery. Hence, this study investigates how banking system security (BSS) and efficiency (EEF) influence perceived service quality (PSQ), with responsiveness (RES) as a mediating factor. Methods: A quantitative cross-sectional survey design was employed using primary data collected from 289 banking customers in Kathmandu metropolitan city together with three municipalities in the northern part of Kathmandu district. The constructs for BSS, EEF, RES, and PSQ were measured using validated scales from previous literature, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test direct and mediating effects. Results: The findings reveal that banking system security significantly influences both responsiveness and perceived service quality. Efficiency positively affects responsiveness but does not directly impact perceived service quality. Responsiveness significantly enhances perceived service quality and mediates the effects of both banking system security and efficiency on perceived service quality, with stronger mediation observed for banking system security. Overall, banking system security emerges as the most influential predictor of perceived service quality. Conclusion: The study finds that security acts both as a direct assurance factor and an indirect experiential factor through responsiveness, while efficiency enhances service quality mainly when its benefits are reflected in responsiveness. For Nepalese banks, key strategies include ensuring visible security, embedding responsiveness into service design, and aligning efficiency with customer-facing outcomes. The findings advance SERVQUAL model by revealing the asymmetric roles of security and efficiency and confirming the mediating role of responsiveness in an emerging market context. Novelty: The research introduces a unified mediation framework integrating security, efficiency, responsiveness, and service quality. Moreover, by merging elements from multiple theories, the study offers a comprehensive model that deepens understanding of service quality in emerging economies.